Kedudukan Wanita Dalam Mewaris Setelah Adanya Keputusan Pesamuhan Agung Iii Majelis Utama Desa Pakraman Bali (Nomor 01/KEP/PSM-3/MDP Bali/X/2010) - Ni Putu Indah Pratiwi; Diah Gayatri Sudibya; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
The survival of a society is guaranteed by marriage, which there is a legal heir. The existence of legal heirs in Indonesia is still not currently legal, as well as unification of Bali from a district with other counties could not be equated the inheritance system. Bali has a fatherly line that ispatrilinial, which causes only the descendants of the kapurusa's status as heir in the family. Then with the decision of the Supreme Pesamuhan III which describes possible female heir or heirs. Formulation of the difficulty in this study is how the situation of women in Bali in Bali where the inheritance in the family embraced the system patrinial and how the position of women of Bali after the promulgation of the decision of the Supreme Pesamuhan III MUDP. The type of research used in this study is normative legal research. Thus the legal heirs in Bali customs, women cannot inherit because she is not capable in undertaking its obligations, whether liability caring for parents or an obligation in customary and ayahan temples. Whereas after the Supreme Pesamuhan III MUDP Bali said women can fully inheriting like male although in that women marrying out but he had to keep running its obligations.